The Effect of Audit Period, Company Age, Auditor Relationship and Public Accounting Firm Reputation on Audit Delay - Kristiani Novita Sari Munthe; Rahmad Oloansyah Pakpahan; Arie Pratania Putri (Budapest International Research and Critics University, 2022)
The purpose of this study is to determine the effect of audit tenure, company age, auditor relationship and public accounting firm reputation on audit delay. This research uses multiple linear regression method, besides that this research uses a descriptive approach. This study uses fifty four companies as the population. In this study, the purposive sampling method is a technique for taking samples used to produce forty-three companies as samples. This study partially shows that audit tenure, company age, and the reputation of a public accounting firm have a negative effect on audit delay and auditor relationships have a positive influence on audit delay. Simultaneously, the results of this study show that there is an influence on audit delay from the variables of audit tenure, company age, auditor relationship and reputation of public accounting firms.